New Water‐Soluble Cluster Compound Zn(en)33[V15Sb6O42(H2O)]⋅ (Ethylenediamine)3⋅10 H2O as a Synthon for the Generation of Two New Antimonato Polyoxovanadates. Issue 21 (21st February 2018) - Mahnke, Lisa K.; Warzok, Ulrike; Lin, Mengxi; Näther, Christian; Schalley, Christoph A.; Bensch, Wolfgang
Abstract: A new antimonato polyoxovanadate Zn(en)3 3 [V15 Sb6 O42 (H2 O)]⋅ 3 en⋅ 10 H2 O (en=ethylenediamine) synthesized under hydrothermal conditions exhibits remarkable solubility in water. Electrospray ionization mass spectrometry (ESI‐MS) investigations on an aqueous solution demonstrate that the cluster core remains fully intact for 72 h. At longer times, slow transformation into a V14 Sb8 O42 cluster is observed. The conversion reaches 50 % after 14 days and is complete after approximately 20 days. The rate of this V15 Sb6 →V14 Sb8 cluster transformation is significantly increased in the presence of ammonium acetate. Applying the new compound as a synthon in the presence of 1, 10‐phenanthroline (phen) led to crystallization of Zn(phen)3 2 [Zn(en)2 V15 Sb6 O42 (H2 O)]⋅ 23 H2 O after a short reaction time, whereas addition of Sb2 O3 led to fast crystallization of (Zn(en)2 (H2 O)2 )(Zn(en)2 )[Zn(en)2 V15 Sb6 O42 (H2 O)]⋅ 8.5 H2 O. In the crystal structure of Zn(en)3 3 [V15 Sb6 O42 (H2 O)]⋅ 3 en⋅ 10 H2 O, the en molecules are seen to be attached to the cluster anion through Sb−N bonds. In the structures of the two new compounds obtained, the [V15 Sb6 O42 (H2 O)] 6− anions are expanded by Zn 2+ ‐centered complexes through Zn−O−V bond formation. Abstract : Cluster synthesis in water : A new water‐soluble hetero‐polyoxovanadate has been prepared, with zinc complexes as charge‐balancing units. Its transformation to two new V15 ‐polyoxovanadates in water is reported.